Conflicts in construction - Whitfield, Jeff (Hoboken, New Jersey : Wiley-Blackwell, 2012)
'The book deals with all types of conflict but concentrates on the conflicts that lead to disputes in construction projects. The book shows the reader how to avoid, manage and resolve conflicts before they become serious disputes'--
Includes index.
Keywords: Construction industry -- Management; Conflict management